Perbandingan Pengetahuan dan Sikap Peduli Lingkungan di Sekolah Kawasan TNWK dengan Perkotaan - Osalia Putri Pertiwi; Dewi Lengkana; Arwin Surbakti (Universitas Lampung, 2019)
This study aims were to compare the knowledge of biodiversity and the environmental care attitude of students between schools around the conservation of TNWK and urban school. This study used descriptive verification and ex post facto design. The samples were X grade IPA students in Seputih Surabaya 1 High School and Bandar Lampung 1 High School 2017/2018 Academic Year which were taken using purposive sampling method. Data on students' knowledge were obtained through tests and environmental care attitudes obtained through questionnaires. Data were analyzed using the t-test and linear regression. The results of t-test showed that there were differences in knowledge significant environmental care attitude towards students in school the TNWK conservation area and school in urban area. The results of the linear regression test showed that there was very strong relationship between knowledge and environmental care for high school in school the TNWK area.Penelitian ini bertujuan membandingkan pengetahuan keanekaragaman hayati dan sikap peduli lingkungan siswa di sekolah konservasi TNWK dengan sekolah perkotaan. Penelitian menggunakan desain deskriptif verifikatif dan ex post facto. Sampel penelitian adalah siswa kelas X IPA di SMA Negeri 1 Seputih Surabaya dan SMA Negeri 1 Bandar Lampung Tahun Pelajaran 2017/2018 yang diambil menggunakan metode purposive sampling. Data pengetahuan diperoleh melalui tes dan sikap peduli lingkungan diperoleh melalui angket. Analisis data menggunakan uji-t dan regresi linear. Hasil uji-t menunjukkan terdapat perbedaan pengetahuan dan sikap peduli lingkungan yang signifikan antara siswa di sekolah kawasan konservasi TNWK dengan sekolah di perkotaan. Hasil uji regresi linear menunjukkan adanya hubungan yang sangat kuat antara pengetahuan dengan sikap peduli lingkungan siswa di sekolah kawasan TNWK. Kata kunci: keanekaragaman hayati, konservasi, perkotaan, sikap peduli lingkungan